Joint control of urban expansion and climate change on urban-rural vegetation phenology gradient in 31 cities of China - Yang, Hao; Zhang, Qiang; Zhang, Songlin; Wang, Xufeng; Yu, Hongyuan (Frontiers in Ecology and Evolution, 2025)
The spatiotemporal heterogeneity of urban vegetation phenology (UVP) has intensified due to coupled urban expansion and climate change, yet the systematic understanding of UVP responses along urban-rural gradients across diverse climatic contexts and urban expansion remains limited. Therefore, this study selected 31 Chinese cities across diverse climate zones and city sizes using multi-source remote sensing data (2001-2020) to quantify the synergistic effects of urban expansion and climate change on urban-rural UVP differences (ΔUVP). First, UVP in China exhibited advanced start of growing season (SOS), delayed end of growing season (EOS), and extended length of growing season (GSL), with more pronounced shifts in southeastern regions compared to northwestern zones. Furthermore, the magnitudes of SOS advancement, EOS delay, and GSL extension gradually decreased along the urban-rural gradient. ΔUVP in large cities was smaller than that in other city sizes, whereas arid and semi-arid zones exhibited significantly greater ΔUVP than humid and semi-humid zones. Second, ΔSOS, ΔEOS, and ΔGSL demonstrated predominantly negative, positive, and positive correlations with both urban heat island intensity (ΔLST) and urban expansion intensity (ΔISP), respectively. Medium cities demonstrated the maximum response magnitudes of ΔUVP to ΔLST compared to other city sizes, whereas small towns demonstrated the maximum response magnitudes of ΔUVP to ΔISP. The response magnitudes of ΔUVP to both ΔLST and ΔISP were significantly greater in arid and semi-arid zones than in humid and semi-humid zones. Finally, principal component analysis confirmed that urban factors predominantly drive ΔUVP variations, with ΔISP identified as the primary regulatory factor. These findings provide critical insights into urban vegetation dynamics under rapid expansion and climate change.